Dominant Positions and Monopolistic Practices in Indonesian Competition Law: Posisi Dominan dan Praktik Monopoli dalam Hukum Persaingan Usaha Indonesia - Avriel Silvio Delano Singal; Dhymaz Satria Pramono; Joseph Hugo Vieri Iusteli Sira Kira (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Competition law in Indonesia aims to safeguard market mechanisms while allowing firms to achieve dominance through legitimate competitive processes. Specific Background Law No. 5 of 1999 adopts a behavioral approach by not prohibiting dominant positions per se but restricting their misuse, with enforcement carried out through analytical frameworks developed by the competition authority. Knowledge Gap However, ambiguity persists in distinguishing lawful market dominance derived from efficiency and innovation from prohibited monopolistic conduct characterized by exclusionary and exploitative practices. Aims This study formulates juridical criteria to clearly differentiate lawful dominance from abuse of dominant position within the Indonesian competition law framework. Results The findings identify three cumulative parameters—objective, method, and impact—as decisive indicators: lawful dominance is driven by efficiency, innovation, and consumer benefit, while abusive conduct aims to eliminate competitors, employs unjustifiable strategies, and generates anti-competitive effects such as restricted market access and reduced consumer welfare. Novelty The study introduces an integrated legal-economic analytical framework combining rule of reason, effects-based approach, and multidimensional assessment to refine legal interpretation. Implications These criteria provide guidance for regulators and businesses to ensure proportional law enforcement, maintain competitive market structures, and support sustainable economic efficiency without hindering legitimate business growth. Highlights: Differentiation is determined by objective, method, and resulting market conditions. Legitimate market control originates from efficiency, innovation, and fair competition. Anti-competitive conduct involves exclusionary strategies and consumer welfare reduction. Keywords: Dominant Position, Monopolistic Practices, Abuse of Dominant Position, Competition Law